E-supply chain integration adoption: examination of buyer–supplier relationships - Zhou, Wangyue; Chong, Alain Yee Loong; Zhen, Cao; Bao, Haijun (Taylor & Francis, 2018)
The purpose of this study is to empirically examine the adoption of e-supply chain integration by electrical and electronic industry suppliers. This study has integrated both the transaction cost and resource-dependence models in understanding the influence of buyer–seller relationships on e-supply chain integration. Hypotheses were developed based on the proposed model. Data were collected from 122 electrical and electronic suppliers located in Malaysia. The data was examined using multiple regression analysis. The results showed that Asset Specificity, Product Technological Uncertainty, Transaction frequency, Proportion of sales to e-supply chain integration promoter, and number of customers are able to explain suppliers’ decisions to adopt e-supply chain integrations with their buyers. Buyers that would like to improve the adoptions of e-supply chain integration will be able to formulate and plan strategies from the buyer–seller relationships perspectives.